2014
DOI: 10.1371/journal.pone.0110586
|View full text |Cite
|
Sign up to set email alerts
|

The Association between a Vegetarian Diet and Cardiovascular Disease (CVD) Risk Factors in India: The Indian Migration Study

Abstract: BackgroundStudies in the West have shown lower cardiovascular disease (CVD) risk among people taking a vegetarian diet, but these findings may be confounded and only a minority selects these diets. We evaluated the association between vegetarian diets (chosen by 35%) and CVD risk factors across four regions of India.MethodsStudy participants included urban migrants, their rural siblings and urban residents, of the Indian Migration Study from Lucknow, Nagpur, Hyderabad and Bangalore (n = 6555, mean age-40.9 yrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 43 publications
8
52
1
4
Order By: Relevance
“…15 In Indian Migration Study, a study of rural and urban adult population, mean aged 40+ years, across four regions and 18 states of India, it was found that vegetarians had lower levels of lipids and blood pressure supporting the hypothesis that a vegetarian diet has potential cardiovascular health benefits. 4 These findings are in par with our study were total cholesterol levels were lower among vegetarians.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…15 In Indian Migration Study, a study of rural and urban adult population, mean aged 40+ years, across four regions and 18 states of India, it was found that vegetarians had lower levels of lipids and blood pressure supporting the hypothesis that a vegetarian diet has potential cardiovascular health benefits. 4 These findings are in par with our study were total cholesterol levels were lower among vegetarians.…”
Section: Discussionsupporting
confidence: 83%
“…4 There has been a rapid increase in coronary artery disease (CAD) in most Asian countries; however, there is no consensus of opinion on diet and lifestyle guidelines and desirable levels of risk factors for prevention of CAD in these countries. 5 The proportion of deaths due to CVDs in Asians may be about 15% and in India CVD accounts for 53.5% of mortality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39] Some trials have reported lowering of high-density lipoprotein cholesterol concentrations and the ratio of total cholesterol to high-density lipoprotein. 40 Vegetarian dietary patterns are characterized as predominantly including fruits, vegetables, whole grains, and nuts, similar to the DASH diet.…”
Section: The Vegetarian Dietary Pattern: Nutrient Dense Variably Defmentioning
confidence: 99%